Biofertilizante bovino e salinidade da água de irrigação no comportamento vegetativo e produtivo do maracujazeiro amarelo. - Dias, Thiago Jardelino (2011)
The accumulation of salts in the soil by irrigation water has caused negative effects on productive capacity and quality of the of crops, including the yellow passion fruit. In this context, the irrigated areas, especially in arid and semiarid regions, require management technologies that maintain the productive capacity of the crops with economic viability, minimizing the depressive effects of management in irrigated areas with water of high salt content. This work had the objective to evaluate the effects of irrigation water salinity (EC) associated to of frequencies application of bovine biofertilizer on the initial growth of seedlings, production, mineral nutrition and postharvest quality of yellow passion fruit and also am soil fertility and salinity. The treatments were distributed in 5 x 4 factorial design corresponding the five EC of irrigation water of 0.5, 1.5, 2.5, 3.5 and 4.5 dS m-1, in four frequencies of application of the biofertilizer: without bovine biofertilizer (SB); with application one week before transplanting (1SAT); application with intervals of 90 days after transplanting (90DAT); and, with application one week before transplanting and at intervals of 90 days (1SAT+90DAT). Plants irrigated with water of electrical conductivity less than 2.5 dS m-1 and application of biofertilizer 1SAT+90DAT showed less impairment of quality of soil, vegetative growth and increased production, as well as foliar concentrations of the crops of yellow passion fruit. The salt concentrations of irrigation water exceeds in 2.5 dS m-1 markedly reduced levels of chlorophyll, but also the absorption of water by plants, raising the percentage of soil moisture. The applications of biofertilizers did not influence the concentration of pigments photosynthetic of passion fruit, however, the highest frequencies of use (90DAT and 1SAT+90DAT) increased the percentage of soil moisture.